Primary rhinoplasty: An Indian perspective - Bhat Uday; Patel Bharat (Indian Journal of Plastic Surgery)
The spectrum of indications for rhinoplasty in Indian patients is very wide. An ill-defined nose with lack of projection and broad osteocartilagenous framework is the commonest problem. A large number of patients require narrowing of the framework by osteotomies, alar wedge resection,and augmentation by a suitable fill, preferably a cartilage graft. The technique of rhinoplasty in Indian patients with special emphasis on cartilage grafting has been discussed here. Cartilage grafts, when used as a fill, produce soft, natural results.